Detection of structural faults in piers of masonry arch bridges through automated processing of laser scanning data. Issue 3 (8th December 2017) - Sánchez‐Rodríguez, A.; Riveiro, B.; Conde, B.; Soilán, M.
Summary: This paper introduces a new methodology for the automated processing of large point clouds for the diagnosis of structural pathologies in piers of masonry arch bridges. This method starts with the automatic segmentation of the global point cloud of the entire bridge in its different structural elements (piers, arches, spandrel walls, etc.). Later, piers were further segmented in order to be able to detect and quantify structural pathologies. Particularly, faults are based in geometric anomalies (tilts and skews) of the pier walls that might be indicators of stability problems of the entire bridge. The methodology was validated using several samples of representative masonry arch bridges. The obtained results demonstrate that this method can provide useful information about the structural health of the bridge requiring neither training in the technology nor advanced knowledge in the processing of laser scanning data.